Genkwanin Prevents Lipopolysaccharide-Induced Inflammatory Bone Destruction and Ovariectomy-Induced Bone Loss - Fu, Xin; Sun, Xiaochen; Zhang, Chenxi; Lv, Nanning; Guo, Huan; Xing, Chunlei; Lv, Juan; Wu, Jiwen; Zhu, Xiaoli; Liu, Mingming; Su, Li (Frontiers in Nutrition, 2022)
Abstract Objectives The first objective was to probe the effect of Genkwanin (GKA) on osteoclast. The second goal of this study wast to study whether GKA can protect LPS and ovariectomized (OVX) induced bone loss. Methods Various concentration of GKA (1mg/kg and 10mg/kg) were injected into mice. Different concentration of GKA (1μM and 5μM) were used to detected the effect of GKA on osteoclast and osteoblast. Key findings GKA attenuated the osteoclast differentiation promoted by RANKL and expression of mark genes containing c-Fos, NFATc1 as well as bone resorption related gene TRAP and to the suppression of MAPK signaling pathway. NFATc1 and bone resorption related gene TRAP and to the suppression of MAPK signaling pathway. Moreover, the GKA prevented LPS-induced and ovariectomized-induced bone loss in mice. Conclusions Our research revealed that GKA had a potential to be an effective therapeutic agent for osteoporosis.